Avaliação da toxicidade da água residuária da usina de beneficiamento da casca do coco verde em girinos de Leptodactylus vastus (Amphibia, anura, leptodactylidae) - Viana, Sidarta Lopes (2010)
Amphibians have several characteristics that make them particularly sensitive bioindicators for environmental quality. In this study, tadpoles of the anuran species Leptodactylus vastus A. Lutz, 1930 were used in bioassays to evaluate the toxicity of the liquid from the coconut shell (LCCV), a byproduct of the processing of the green coconut shell. It was analyzed acute effects as lethality and chronic effects as changes in the rate of metamorphosis, in the length of the larval period and in the mass of the tadpoles at metamorphosis. It was performed a total of six experiments, each lasting ninety days, using both LCCV extracted from fresh coconut shells still greenish and LCCV extracted from dry coconut shells that had already became yellowish. The first four experiments had seven treatments each, with concentrations of 0% (control), 0,1%, 0,2%, 0,3%, 0,4%, 0,5% and 0,6% of LCCV. The other two experiments had six treatments each, with concentrations of 0% (control); 0,3%; 0,6%; 0,9%; 1,2% and 1,5% of LCCV. Each treatment had three replicates with ten tadpoles each. The tadpoles were collected at Campus do Pici, Fortaleza, Ceará, in different places and days to avoid pseudo-replication in space and time. The LCCV had a toxic effect on the tadpoles of Leptodactylus vastus, causing an increase in mortality and a decrease in size at metamorphosis, in the highest concentrations tested. However, in some intermediate concentrations, the LCCV contributed to an increase in the mass of tadpoles during metamorphosis. Moreover, in the concentrations tested, the LCCV did not affect the ability of surviving tadpoles to complete metamorphosis or the length of the larval period. Tadpoles of L.vastus showed a positive correlation between mass at metamorphosis and length of the larval period, except in the highest concentrations tested. These results indicate that the LCCV can negatively affect the biota of aquatic environments, making necessary to determine safe parameters of its emission to the environment. The tadpoles of Leptodactylus vastus showed a good potential for use in ecotoxicological studies and as bioindicators of disturbance in aquatic environments, as L.vastus is a quite common species that it is not under threat or danger of extinction, and that produce conspicuous ovipositions with many eggs and larvae relatively large and easily manipulated as they do not require aeration or filtration of water or a special diet.